Amikacin Liposome Inhalation Suspension for Treatment-Refractory Lung Disease Caused by Mycobacterium avium Complex (CONVERT). A Prospective, Open-Label, Randomized Study - Griffith, David E.; Eagle, Gina; Thomson, Rachel; Aksamit, Timothy R.; Hasegawa, Naoki; Morimoto, Kozo; Addrizzo-Harris, Doreen J.; O’Donnell, Anne E.; Marras, Theodore K.; Flume, Patrick A.; Loebinger, Michael R.; Morgan, Lucy; et al. (American journal of respiratory and critical care medicine, 2018)
Improved therapeutic options are needed for patients with treatment-refractory nontuberculous mycobacterial lung disease caused by complex (MAC). To evaluate the efficacy and safety of daily amikacin liposome inhalation suspension (ALIS) added to standard guideline-based therapy (GBT) in patients with refractory MAC lung disease. Adults with amikacin-susceptible MAC lung disease and MAC-positive sputum cultures despite at least 6 months of stable GBT were randomly assigned (2:1) to receive ALIS with GBT (ALIS + GBT) or GBT alone. Once-daily ALIS was supplied in single-use vials delivering 590 mg amikacin to the nebulizer. The primary endpoint was culture conversion, defined as three consecutive monthly MAC-negative sputum cultures by Month 6. Enrolled patients (ALIS + GBT, = 224; GBT-alone, = 112) were a mean 64.7 years old and 69.3% female. Most had underlying bronchiectasis (62.5%), chronic obstructive pulmonary disease (14.3%), or both (11.9%). Culture conversion was achieved by 65 of 224 patients (29.0%) with ALIS + GBT and 10 of 112 (8.9%) with GBT alone (odds ratio, 4.22; 95% confidence interval, 2.08-8.57; < 0.001). Patients in the ALIS + GBT arm versus GBT alone were more likely to achieve conversion (hazard ratio, 3.90; 95% confidence interval, 2.00-7.60). Respiratory adverse events (primarily dysphonia, cough, and dyspnea) were reported in 87.4% of patients receiving ALIS + GBT and 50.0% receiving GBT alone; serious treatment-emergent adverse events occurred in 20.2% and 17.9% of patients, respectively. Addition of ALIS to GBT for treatment-refractory MAC lung disease achieved significantly greater culture conversion by Month 6 than GBT alone, with comparable rates of serious adverse events. Clinical trial registered with www.clinicaltrials.gov (NCT02344004).